Changes in the Essential Oil Content and Composition of Lippia citriodora under Vacuum Oven-drying and Pre-drying Operation - Ali Rezvani Aghdam; Hassanali Naghdi Badi; Vahid Abdossi; Reza Hajiaghaee; Seyed Ebrahim Hosseini (Institue of Medicinal Plants, ACECR, 2019)
Background: Pre-drying operations and drying methods have a significant effect on the quantity and quality of plants essential oils. Objective: In this study, the effect of pre-drying operation and vacuum oven-drying was investigated on the essential oil content and composition of Lippia citriodora. Method: This research was conducted as a factorial experiment in a completely randomized design (CRD) with three replications. The two studied factors were (1) pre-drying operations in two levels including pre-drying and without pre-drying operation, and also (2) drying methods in 5 levels including fresh plant, shade drying and vacuum oven-drying at 35, 45 and 55°C at 0.5 bar atmospheric pressure.  In this study, the amount of pigments and essential oil content and composition were measured. Results: The results indicated that the highest chlorophyll content was related to treatment of vacuum oven-drying at 55 °C with a pre-drying treatment, while the highest amount of essential oil was obtained by vacuum oven-drying at 45 °C without a pre-drying operation. The highest amounts of monoterpene hydrocarbons, oxygenated monoterpenes, and geranial were obtained by drying at 55 °C, while the highest content of sesquiterpene hydrocarbons, oxygenated sesquiterpenes and neral were observed in Low-temperature drying. Conclusion: In general, this study indicated that vacuum oven-drying at 45 °C was the best drying method for obtaining maximum content of essential oil and active components.